Hierarchical decision making patterns for the placement of physical supply chain entities - Phiroz, Zal Navroze (Research of GSB, 2018)
One of the most important areas of development within the evolution of commerce, is the acknowledgement that businesses can no longer compete as individual entities, but rather must function as part of a supply chain. Within an ever-competitive business environment, the ultimate success of a business can often be tied directly to the overall functionality and efficiency of its supply chain. Research within the area of supply chain management is vast, with prior contributions exploring the function of a supply chain from a plethora of social, economic, and commerce perspectives. Prior research has extended to evaluate multiple industries and geographies, over a number of economic and social issues (e.g. environmental sustainability through transport route modification, poverty reduction through global value chain refinement), along with core management and commerce areas (e.g. marketing initiatives through production cycle analysis, operations management through production capacity). Substantial contributions exist which focus on the role of supply chain management and the value of refining, optimizing and designing a chain to the requirements of an industry, economic environment, or business process. In addition to investigation on the definition, function, and applicability of the concept, prior contributions have effectively demonstrated the value of supply chain management in gaining competitive advantage, and improving the overall performance of a business. The notion that supply chain efficiency defines business advantage, has led to exploration of physical configurations and specifications of supply chains; with the primary undertone often centering around evaluating drivers of supply chain optimization, and therein organizational performance. Within existing research, the process of physical site placement, and managerial decision makers within an organization are identified as being key factors in the optimization of a supply chain. As such, a number of prior studies have investigated the drivers which influence physical location decisions, with the majority of research focusing on the impact of geographical location factors. Other studies have centered on the impact of management structure as a catalyst in refining and optimizing a supply chain. While significant research has focused on both areas individually (Barney, 1991; Chopra & Meindl, 2002; Christopher, 1998), relatively little attention has been placed on evaluating the correlation between these paradigms, and therein exploring the root drivers for management decisions. There appears to be substantial value in directly investigating this relationship, as the analysis of this interaction would provide a comprehensive interpretation of specific factors contributing to physical supply chain development decisions. This research evaluated decision making drivers impacting the placement of physical supply chain entities using augmented qualitative and quantitative primary data. One of the main objectives of this study was to define the accepted sequence of decision making priority with respect to land value determination, transportation and accessibility considerations, and tax incentive structures. Data for the study was collected through electronic surveys and interviews, from supply chain managers working at organizations with a minimum annual revenue of $1,000,000 USD. The proposed relationships were evaluated using rigorous statistical analysis including factor analysis and structural equation modelling. Results indicated the existence of a clear sequence in decision structure, with a measurable pattern of priority placed on specific decision criteria. Aspects of corporate culture within the scope of supply chain decision making were explored with insight into the foundation for physical site evaluation. Empirical data suggested the value of land as having the most substantial influence when making physical location decisions. A number of factors influence how managers determine land value, however the location of a site and its proximity to a firms affiliates (e.g. potential partners, strategic alliances) were identified as having the strongest impact. Other considerations including transportation structures, tax incentives, and the ability of a firm to attract highly productive labor also influenced location decisions, albeit to a lesser degree. While prior research suggests businesses often design supply chains with the intention of attracting inexpensive labor, the results of this study were contradictory. Specifically, this study identified a common hierarchical decision making structure, and finds businesses often place value on highly productive labor (not inexpensive labor) when making supply chain location decisions. Fundamentally, the results presented in this study allows firms to gain insight on how decision makers process and interpret information. Establishing the pattern and sequence of decision making priority in the initial physical site placement stage is critical in ascertaining how supply chain networks develop and grow. From an economic standpoint, findings from this study could be applied to competitor assessment, growth planning, and managerial assessment. Based on the notion that competition takes place through supply chain performance, the practical applications of this study provide a meaningful foundation for optimization and therefore competitive advantage. On a larger scale, this contribution is substantial, as it holds value to both academic and business paradigms in further evaluating the definition and optimization potential of a supply chain, and in providing insight into additional areas of business competitiveness.